2021
DOI: 10.3390/toxins13040248
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone and the Immune Response

Abstract: Zearalenone (ZEA) is an estrogenic fusariotoxin, being classified as a phytoestrogen, or as a mycoestrogen. ZEA and its metabolites are able to bind to estrogen receptors, 17β-estradiol specific receptors, leading to reproductive disorders which include low fertility, abnormal fetal development, reduced litter size and modification at the level of reproductive hormones especially in female pigs. ZEA has also significant effects on immune response with immunostimulatory or immunosuppressive results. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 150 publications
(200 reference statements)
1
53
0
5
Order By: Relevance
“…Although several reports have indicated that ZEA has either stimulating or suppressing effects on innate immunity [ 17 , 18 ], the cellular mechanisms activated by ZEA in triggering innate immune responses in macrophages during pathogen infection are not yet well understood. The present study investigated the effects of ZEA on the activities of innate immune responses during pathogen infection by macrophages in vitro and ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports have indicated that ZEA has either stimulating or suppressing effects on innate immunity [ 17 , 18 ], the cellular mechanisms activated by ZEA in triggering innate immune responses in macrophages during pathogen infection are not yet well understood. The present study investigated the effects of ZEA on the activities of innate immune responses during pathogen infection by macrophages in vitro and ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, SM was The concentrations of the pro-inflammatory cytokines were not altered by the exposure of the PBMC to ZEA, with the exception of TNF-a concentration that was significantly decreased (p<0.05) after 48h exposure to the toxin. Literature data concerning inflammatory effect of ZEA are controversial as in vitro or in vivo studies have shown an increase or a decline of inflammatory response induced by ZEA depending on the cell type or organ (Bulgaru et al, 2021). In PBMC cells treated with both toxin and sea buckthorn meal extract, SM was able to decrease the synthesis of IL-6 (by 7.8 times) and IL-8 (by 1.3 times), but not of TNF- and IL-1 .…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines, including IL-1, IL-3 and IL-6, play pivotal roles in crosstalk between inflammation and coagulation [ 61 , 62 , 63 ]. Previous research indicates that ZEN can affect the secretion of the above factors [ 23 , 64 , 65 , 66 ]. However, so far, the effect of cytokines on the vascular system has not been linked to ZEN exposure.…”
Section: Discussionmentioning
confidence: 99%